The Effect of Single Dose Dexamethasone on Postoperative Pain and Post Operative Nausea Vomiting in Patients Undergoing Breast Surgery Under General Anaesthesia - Laila Khalid, Khawar Aziz, Aqil Qayoom, Muhammad Sirajuddin, Ali Asghar, Ayesha Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The primary purpose of this study is to assess the efficacy of intravenous dexamethasone in preventing postoperative nausea and vomiting in patients who have had breast surgery under general anesthesia. Methods: After ethical approval from institution review board, this randomized control was carried out at Liaqat national hospital and medical college. Seventy-four patients who completed the study’s criteria and provided written informed permission were enrolled in a random order. Patients were recruited and then randomly assigned through balloting without replacement to one of two groups: (A) dexamethasone (n = 37) or (B) placebo (n = 37). After general anesthesia, patients in Group received 0.1mg/kg of dexamethasone intravenously at the same time. Patients in Group B received a placebo (2 ml of normal saline 0.9% at the same time following general anesthesia). Mean arterial blood pressure (MAP), heart rate (HR), respiration rate (RR), and the intensity of pain and vomiting was measured at 0 (in the operating room), 30, 60, and 120 minutes, and 4-, 6-, 12-, and 24-hours following surgery. Results: The mean age of the participants in both study groups were 48.56±15.25 and 50.4±16.8 years. The mean anesthesia time of the participants in both study groups were 114±9.6 and 122.7±8.7 minutes. The mean surgery time of the participants in both study groups were 88.2±2.1 and 96.1±3.72 minutes. No significant difference in the heart rate (HR) was observed in both study groups at any time interval. A significant difference in the heart rate was observed in both study groups at 6-, 12-, and 24-hours’ time interval. A significant difference in the heart rate was observed in both study groups at 0 and 30 minutes, 1-,2-,4-, 6-, 12-, and 24-hours’ time interval. Conclusion: There were no notable changes in vital signs associated with the use of intravenous dexamethasone for the treatment of postoperative pain, the need for rescue analgesia on postoperative day 1, or the occurrence of postoperative nausea and vomiting. Keywords: Visual analog score, nausea, vomiting, pain, dexamethasone